Addressing the Implementation Crisis: Securing Reparation and Righting Wrongs. (7th September 2020) - Murray, Rachel
Abstract: There has been increasing attention to the implementation of decisions of human rights bodies by scholars and by supranational institutions, states, litigants, and civil society. A project funded by the Economic and Social Research Council (ESRC) tracked the implementation by nine states of decisions adopted by human rights courts and commissions in the European, African and Inter-American systems and by select UN treaty bodies. This article summarizes the methodology and findings of the Project and in so doing forms an introduction to a series of articles and practice notes published in this special issue. A range of factors are identified from the research which influence implementation and stress the importance of a multifaceted, multidimensional approach to the issues. Implementation is not automatic and requires mechanisms, processes, and the involvement of actors (national and supranational) for states to comply with the reparations ordered in the decision. A case-by-case, state-by-state, context-specific approach is needed, tailored to the circumstances. This has implications for the manner in which litigants present their submissions, engage with state and supranational bodies and for the latter in terms of their roles and relationships with the various actors.